2017
DOI: 10.1186/s12864-017-4198-0
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of smoking-related disturbed methylation: a two time-point study of methylation change in smokers, non-smokers and former smokers

Abstract: Background: The evidence for epigenome-wide associations between smoking and DNA methylation continues to grow through cross-sectional studies. However, few large-scale investigations have explored the associations using observations for individuals at multiple time-points. Here, through the use of the Illumina 450K BeadChip and data collected at two time-points separated by approximately 7 years, we investigate changes in methylation over time associated with quitting smoking or remaining a former smoker, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 53 publications
(76 reference statements)
5
71
3
1
Order By: Relevance
“…Others have reported reversion of smoking-associated DNA methylation changes in former smokers persisting beyond 30 years from cessation, with the most rapid reversion rates occurring in the within the first 14 years [26]. Moreover, increased methylation levels at AHRR has been reported in smokers undergoing cessation therapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported reversion of smoking-associated DNA methylation changes in former smokers persisting beyond 30 years from cessation, with the most rapid reversion rates occurring in the within the first 14 years [26]. Moreover, increased methylation levels at AHRR has been reported in smokers undergoing cessation therapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the most interesting finding from this study was that, on average, PTSD cases, relative to controls, had lower methylation at several CpG sites in the AHRR gene when compared to trauma-exposed controls. Methylation of AHRR CpGs has been strongly linked to smoking [29][30][31] . As substantially more of the PTSD cases reported smoking compared to controls, this suggested that we should control for smoking in the EWAS.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have investigated the effect of time since quitting smoking on blood DNA methylation (62,63), the potential effect of past smoking on the methylation of the placenta had not been explored. We focused on women who had smoked but quitted smoking before their pregnancy and therefore before the differentiation of the placenta.…”
Section: Possible Explanationsmentioning
confidence: 99%